Digitalization of Public Services in Nepal: An Assessment of the Implementation Status - Rajkarnikar, Rashmee (Nepalese Journal of Economic Studies, 2025)
Information and Communication Technology (ICT) had developed rapidly during the past decade. COVID-19 pandemic has triggered digitized delivery of public services throughout the world as lockdowns and social distancing became the norm. As the internet became a virtual medium that enabled people to communicate from anywhere, and remotely implementing public services delivery and welfare schemes has been necessary. Nepal’s journey of e-governance is strengthened by key policy frameworks designed to enhance digital transformation. Effective practice of E- governance is possible only in using ICT in the delivery of public service, which demands public participation and citizen centric administration. This paper explores the current status of implementation of the digitized public services in Nepal. On-line survey technique was executed to collected data and information on current status of public service delivery. The ‘Strategic Framework Model’ was adapted for assessing the current state of implementation of digitized public services at local government level. ‘Assessment Matrix’ was devised to collect the information from 80 master level college students. The result of the assessment shows Insufficient IT infrastructure, Low Digital Literacy Rate, limited IT human resources, and existence of digital divide. Thus, digital transformation of public services requires improvement in digital literacy, ensuring affordable and reliable access, and implementing robust online safety measures. JEL Classification: E60, H41, P43